DATA PREPARATION ON LARGE DATASETS FOR DATA SCIENCE - Barapatre, Darshan; A, Vijayalakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â According to interviews and experts, data scientists spend 50-80% of the valuable time in the mundane task of collecting and preparing structured or unstructured data, before it can be explored for useful analysis. It is very valuable for a data scientist to restructure and refine the data into more meaningful datasets, which can be used further for analytics. Hence, the idea is to build a tool which will contain all the required data preparation techniques to make data well-structured by providing greater flexibility and easy to use UI. Tool will contain different data preparation techniques which will include the process of data cleaning, data structuring, transforming data, data compression, and data profiling and implementation of related machine learning algorithms.